2018
DOI: 10.3390/md16010007
|View full text |Cite
|
Sign up to set email alerts
|

Toxicology of Gambierdiscus spp. (Dinophyceae) from Tropical and Temperate Australian Waters

Abstract: Ciguatera Fish Poisoning (CFP) is a human illness caused by the consumption of marine fish contaminated with ciguatoxins (CTX) and possibly maitotoxins (MTX), produced by species from the benthic dinoflagellate genus Gambierdiscus. Here, we describe the identity and toxicology of Gambierdiscus spp. isolated from the tropical and temperate waters of eastern Australia. Based on newly cultured strains, we found that four Gambierdiscus species were present at the tropical location, including G. carpenteri, G. lapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 84 publications
(141 reference statements)
0
50
0
Order By: Relevance
“…The assay was shown to be highly sensitive and accurately detected 0.05 to over 4000 cells for G. lapillus. Although the toxin profile of G. lapillus has not been completely defined, it may produce uncharacterised CTXs congeners [19,48] and therefore is a part of the ciguateric web in Australia. The assay was applied to spatial replicates from 25 sites around Heron Island on the GBR, which found that G. lapillus was commonly present, but had a patchy spatial distribution and abundance.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The assay was shown to be highly sensitive and accurately detected 0.05 to over 4000 cells for G. lapillus. Although the toxin profile of G. lapillus has not been completely defined, it may produce uncharacterised CTXs congeners [19,48] and therefore is a part of the ciguateric web in Australia. The assay was applied to spatial replicates from 25 sites around Heron Island on the GBR, which found that G. lapillus was commonly present, but had a patchy spatial distribution and abundance.…”
Section: Resultsmentioning
confidence: 99%
“…More importantly, this assay does not require the operator to rely on melt curves to identify species, or to have access to G. lapillus DNA extracts as a positive control. Due to the potential CTX production of G. lapillus [19,48] the presence and distribution of this species is of interest in Australia where the causative organism(s) for CFP is yet to be established.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the last decade these species have been reported not only from tropical and subtropical waters, but also from more temperate regions, including the coastal waters of New South Wales, Australia [20,[25][26][27][28], and additional species have been reported from more sites throughout the Pacific region ( Figure 1) [6,13,23]. Of the eighteen described Gambierdiscus species, only G. silvae and G. carolinianus have not been reported in the Pacific region.…”
Section: Global Distributionmentioning
confidence: 99%